2014
DOI: 10.1186/1471-2393-14-45
|View full text |Cite
|
Sign up to set email alerts
|

Women’s perception of quality of maternity services: a longitudinal survey in Nepal

Abstract: BackgroundIn the context of maternity service, the mother’s assessment of quality is central because emotional, cultural and respectful supports are vital during labour and the delivery process. This study compared client-perceived quality of maternity services between birth centres, public and private hospitals in a central hills district of Nepal.MethodsA cohort of 701 pregnant women of 5 months or more gestational age were recruited and interviewed, followed by another interview within 45 days of delivery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
55
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 48 publications
15
55
1
Order By: Relevance
“…Physical access as an important barrier to service use in rural Haiti was also demonstrated in previous research that measured access with the distance to the nearest facility reported by key community informants 23 . Our finding also agrees with previous research that having physical access to services is a strong determinant of use of delivery care 28 , 34 36 …”
Section: Discussionsupporting
confidence: 91%
“…Physical access as an important barrier to service use in rural Haiti was also demonstrated in previous research that measured access with the distance to the nearest facility reported by key community informants 23 . Our finding also agrees with previous research that having physical access to services is a strong determinant of use of delivery care 28 , 34 36 …”
Section: Discussionsupporting
confidence: 91%
“…This community thought quality of health care was better in private facilities compared to government ones, which is also reported elsewhere, 34,35 and reduces utilisation of services as well. 36 Indeed, it is well known that the poor attitudes of health workers towards patients, including pregnant women, is a major contributory factor in shunning of facilities.…”
Section: Discussionsupporting
confidence: 77%
“…The pervasiveness of disrespect and abuse in facility‐based birth care has recently been highlighted as a barrier to care in many settings, and there is evidence suggesting this may be a more powerful deterrent to skilled birth attendance than other more commonly recognized barriers such as distance and cost . Multiple factors may contribute to unfriendliness of staff or lack of respectful care, including under‐equipped health facilities, overwhelmed or underpaid health care workers, lack of guidance and supportive supervisions, and an attitude of disrespect for patients that permeates the health system …”
Section: Discussionmentioning
confidence: 99%